What We Say Goes: Conversations on Us Power in a Changing World - Chomsky, Noam; Interviews with Barsamian, David (London Penguin Books, 2007)
In this all-new collection of conversations, Noam Chomsky explores immediate and urgent international concerns including Iran's challenge to the United States, the deterioration of the Israel-Palestine conflict, the ongoing occupations of Iraq and Afghanistan, the rise of China, and the growing power of the left in Latin America, as well as the Democratic victory in the US midterm elections and its ramifications for the future. As always, Chomsky presents his own ideas vividly and accessibly, with uncompromising principles and valuable insights. These interviews will inspire a new generation of readers, as well as long-term Chomsky fans eager for his latest thinking on the many crises the world now confronts.
Includes Notes and Index.
Keywords: Diplomatic relations